Development of the Dictionary of Sharia Economic Law as a Teaching Material: A Comparative Study between the Maqāṣid al-Sharī'ah Approach and the Qawā’id Fiqhiyyah - Arifin, Moch. Zainul; Rohman, Moh. Faizur; Solikin, Agus; Mardiyanto, Ibnu; Ali, Mohammed Ramadhan Abraheem Alshaykh (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2025)
This research aims to develop a Dictionary of Sharia Economic Law Terms as a supporting teaching material in understanding the term fiqh al-mu’amalah and analyze its development based on the perspective of maqāṣid al-sharī'ah and qawā’id fiqhiyyah. The research uses a qualitative approach with the type of research and development (R&D). The dictionary development process is carried out through the planning stages, identification of reference sources, preparation of lemmas, provision of term meanings, and evaluation through Focus Group Discussion (FGD) involving Arabic students and language experts. Data were collected through documentation studies, observations, and focus group discussions, then analyzed using qualitative descriptive methods and normative-conceptual analysis. The results of the study show that the Dictionary of Sharia Economic Law Terms developed is systematically compiled based on classical and contemporary fiqh sources and contains fiqh al-muamalah terms that are relevant to the learning needs of students. The results of the trial show that this dictionary is effective in helping students in understanding the term fiqh al-muamalah, especially in the Sharia Economic Law Book Study course. Analysis based on maqāṣid al-sharī'ah shows that the development of dictionaries is in line with the goal of preserving religion (ḥifẓ al-dīn) and preserving reason (ḥifẓ al-'aql), while analysis based on qawā’id fiqhiyyah shows relevance to the principles of al-mashaqqah tajlib al-taysīr and al-umūr bi maqāṣidihā. Thus, the development of this dictionary has a practical and theoretical contribution in supporting the ease of learning and improving the quality of understanding of terms in the field of Sharia Economic Law.